Ex Libris J. Šapiro - Tammsaar, Jaan (1949- ).; Šapiro, Josifas I. (1921-2004). (1988)
Baszta Giedymina w Wilnie, napis: Ex Libris J. Šapiro.
Data według inwentarza zbioru ekslibrisów PAN BG.
Keywords: Ekslibrisy -- Estonia -- 20 w